2009
DOI: 10.1111/j.1469-7580.2009.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Iliac cortical thickness in the neonate – the gradient effect

Abstract: Recent studies of the neonatal ilium are beginning to reveal that a recognizable structural patterning of trabecular bone is present in the absence of any direct stance-related weight transfer. However, little is known about the organization of compact bone in the ilium and the way in which it is laid down during the earliest stages of development. This study investigates cortical bone thickness across both gluteal and pelvic iliac shells in the human neonatal ilium. Measurements of specific regions of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Most recently, a study investigating the cortical arrangement of the neonatal ilium has added data regarding early variation in cortical thickness. This study demonstrated a graded pattern of cortical bone thickening in line with the expected growth pattern achieved through normal appositional ossification and developing muscle mass, that is, more peripheral regions showed thinner cortices, whereas more central areas displayed a generally thicker cortex (Cunningham and Black, 2009c). This communication builds upon these previous studies by further investigating both the cortical and trabecular structure of the neonatal ilium by analyzing specific relationships between adjacent volumes of interest (VOI).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Most recently, a study investigating the cortical arrangement of the neonatal ilium has added data regarding early variation in cortical thickness. This study demonstrated a graded pattern of cortical bone thickening in line with the expected growth pattern achieved through normal appositional ossification and developing muscle mass, that is, more peripheral regions showed thinner cortices, whereas more central areas displayed a generally thicker cortex (Cunningham and Black, 2009c). This communication builds upon these previous studies by further investigating both the cortical and trabecular structure of the neonatal ilium by analyzing specific relationships between adjacent volumes of interest (VOI).…”
supporting
confidence: 71%
“…4). The method applied for thickness assessment is documented in a previous communication (Cunningham and Black, 2009c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process relies on the delivery of osteogenic components via vascular invasion of the ossifying cortex to form trabecular bone (Laurenson, ). It is considered that growth of the ilium is highly influenced by the space occupying requirements of the vasculature that meet the demands of the active metaphyseal growth fronts (Cunningham and Black, ).…”
mentioning
confidence: 99%
“…Surface mesh (linear triangular shell element) was used to model cortical bone, and volume mesh (linear tetrahedral solid element) to fill cancellous bone and cartilage volumes. Average uniform cortical thicknesses of 0.3 mm and 2.15 mm were considered for the pelvis and leg components respectively. The cortical‐cancellous bony structures closely behave like sandwich structures having a perfect bond between their components.…”
Section: Methodsmentioning
confidence: 99%